Surface heterogeneity: Information from inverse gas chromatography and application to model pharmaceutical substances. (August 2016) - Lapčík, Lubomír; Otyepka, Michal; Otyepková, Eva; Lapčíková, Barbora; Gabriel, Roman; Gavenda, Aleš; Prudilová, Barbora
Abstract: The general theory of electrokinetic phenomena strictly applies to ideal and rigid surfaces or particles. However, many interfaces are non-ideal with respect to both the surface smoothness and surface homogeneity. Detailed knowledge and understanding of the interface structure is often required for proper analysis of electrokinetic measurements. In this study, we investigate the option of studying surface heterogeneity using powder polycrystalline active pharmaceutical ingredients (APIs) as our model systems. We characterized these by a combination of physicochemical techniques, i.e. inverse gas chromatography surface energy analysis, SEM, thermal analysis and powder rheology, to assess the surface interface structure, topology, roughness, chemical heterogeneity and cooperative macroscopic behaviour. The latter characteristics are reflected in the three dimensional packing, which, in turn, affects the porosity and rigidity of the obtained powder bed. Such information is also of paramount interest for realizing proper fluid transport and dispersing or tableting API substances in the pharmaceutical industry. Notably, the 3D packing is affected not only by geometrical characteristics of the powders but also by the polarity and surface charge distribution. These characteristics can be correlated with surface energy data by means of surface energy profiles and surface energy distribution plots. Graphical abstract: Highlights: Surface energy analysis (iGC) provides complex information on surface energy. There were constructed surface energy distributions and surface energy profiles. Detailed interface structure was obtained by surface energy evaluation. It is used to predict macroscopic cooperative powder rheological performance.